2020
DOI: 10.3390/w12061815
|View full text |Cite
|
Sign up to set email alerts
|

The Trend in the Risk of Flash Flood Hazards with Regional Development in the Guanshan River Basin, China

Abstract: The economic development of China’s mountainous areas has been rapid, but the impact of flash floods is often ignored during regional development planning. Therefore, a method needed to be developed to simulate flash flood disasters and analyze the trends in flash flood disasters with regional development. Taking Guanshan River Basin as the research area, we combined the digital elevation model (DEM) with the inflow hydrograph, using the topography-based hydrological model (TOPMODEL). Verified by historical fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The modeling of flash floods is a crucial tool for managing and mitigating floods [1,[37][38][39][40][41][42]. Numerous studies have mapped flood-prone areas using a variety of methodologies, such as [9,[43][44][45][46] have used traditional morphometric analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of flash floods is a crucial tool for managing and mitigating floods [1,[37][38][39][40][41][42]. Numerous studies have mapped flood-prone areas using a variety of methodologies, such as [9,[43][44][45][46] have used traditional morphometric analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers indicated that, the morphological parameters of the basins are the most significant factors affecting the strength of the flood hydrograph and should be considered in any flash flood risk assessment studies [2][3][4]. To estimate the flash flood hazard degrees based on hydro-morphological parameters, a decision-making tool such as Multi-Criteria Analysis Technique (MCA) has been widely used [3,[5][6][7][8]. One of these MCA techniques is the Multi-Attribute Utility Theory (MAUT).…”
Section: Introductionmentioning
confidence: 99%
“…Agrawal studied the relationship between flood risk and resilience in terms of exposure, susceptibility, and lack of coping capacity [ 9 ]. Chen studied the mountain torrents in the Guanshan River Basin and found that with the development of the economy and the migration of population, the risk of mountain torrents is increasing [ 10 ]. Based on the conclusions drawn by most scholars, it can be found that the influencing factors that cause or destroy the vulnerability of flooding and waterlogging mainly include geography, nature, society, and human behavior, among which human behavior has a greater influence, and the influence caused by a combination of many factors is more serious.…”
Section: Introductionmentioning
confidence: 99%